METHODOLOGICAL APPROACHES TO INTEGRATING TOOLS IN ACADEMIC WRITING: THE GLOBAL RISE OF OBESITY - Gulomova Nodira Baxtiyor qizi; Ishqobilova Xulkar Shaydullayevna (TILSHUNOSLIKDA ANTROPOSENTRIZM: YANGI YONDASHUVLAR VA TADQIQOTLAR MAVZUSIDAGI RESPUBLIKA ILMIY-AMALIY ANJUMAN, 2026)
In the period of increasing global problems, obesity has become one of the most pressing issues. This article examines that overweight and its fundamental contributing factors, especially social, economic, and environmental causes. These include widespread consumption of processed, high-calorie, and junk foods, the sedentary lifestyle resulting from technological advancement, and the lack of sufficient knowledge about proper nutrition and a healthy way of living amid people. In addition, the article discusses the drawbacks of obesity, such as the growth of chronic illnesses including sugar diabetes and cardiovascular vessel diseases, as well as the poor quality of life. Furthermore, the efficient solutions and useful recommendations are offered to implement this issue. These contain prioritizing healthy eating habits, doing consistent physical activities, addressing government regulations and reinforcing policies related to the food industry, and ensuring that the population is well-informed and educated about this topic. Overall, the article emphasizes the need for collective and strategic actions of preservation the global problem obesity.